Metalanguage as argumentative strategy in digitaltexts - Roberlei Alves Bertucci (Texto Digital, 2019)
In this work, we aim to analyze metalinguistic resources in digital texts posted by A Capa “newspaper”, a Facebook page which posts multimodal texts, triggering readers’ reflections about daily subjects. Based on Culioli and Normand’s (2005) discussions on language knowledge, we argue that metalanguage is a rational and conscient activity. We assume that it is directly related to identity argument, proposed by Perelman and Olbrechts-Tyteca (2014), since it appears under expressions of definition or classification about language. By analyzing A Capa posts we argue that metalanguage is indeed an important argumentative strategy, which can drive reader to the conclusion intended by the “newspaper without newspaper”.Abstract: In this work, we aim to analyze metalinguistic resources in digital texts posted by A Capa “newspaper”, a Facebook page which posts multimodal texts, triggering readers’ reflections about daily subjects. Based on Culioli and Normand’s (2005) discussions on language knowledge, we argue that metalanguage is a rational and conscient activity. We assume that it is directly related to identity argument, proposed by Perelman and Olbrechts-Tyteca (2014), since it appears under expressions of definition or classification about language. By analyzing A Capa posts we argue that metalanguage is indeed an important argumentative strategy, which can drive reader to the conclusion intended by the “newspaper without newspaper”.